Design and Test of a New Three-Phase Multilevel Inverter for PV System Applications - Nouaiti, A.; Saad, A.; Mesbahi, A.; Khafallah, M.; Reddak, M. (Engineering, Technology & Applied Science Research, 2019)
This paper presents a test of a new three-phase multilevel inverter for PV system applications with reduced number of used DC sources and power switches. The topology of the inverter is designed using an electric assemblage of a two-level dc-dc boost converter (TLBC) with a simplified three-phase multilevel DC-AC converter (THPMC). The TLBC generates two balanced output DC voltages, while the THPMC converts these two DC voltages and generates three-phase AC voltages with five levels per line. Two modulation control techniques are used and tested with the proposed PV system on PSIM and on ISIS Proteus software. The achieved results prove the simplicity and efficiency of the proposed three-phase inverter.